Interdisciplinary assessment of sea-level rise and climate change impacts on the lower Nile delta, Egypt - Sušnik, Janez; Vamvakeridou-Lyroudia, Lydia S.; Baumert, Niklas; Kloos, Julia; Renaud, Fabrice G.; La Jeunesse, Isabelle; Mabrouk, Badr; Savić, Dragan A.; Kapelan, Zoran; Ludwig, Ralf; Fischer, Georg; Roson, Roberto; et al. (Science of The Total Environment, 2015)
CLImate-induced changes on WAter and SECurity (CLIWASEC) was a cluster of three complementary EC-FP7 projects assessing climate-change impacts throughout the Mediterranean on: hydrological cycles (CLIMB — CLimate-Induced changes on the hydrology of Mediterranean Basins); water security (WASSERMed — Water Availability and Security in Southern EuRope and the Mediterranean) and human security connected with possible hydro-climatic conflicts (CLICO — CLImate change hydro-COnflicts and human security). The Nile delta case study was common between the projects. CLIWASEC created an integrated forum for modelling and monitoring to understand potential impacts across sectors. This paper summarises key results from an integrated assessment of potential challenges to water-related security issues, focusing on expected sea-level rise impacts by the middle of the century. We use this common focus to illustrate the added value of project clustering. CLIWASEC pursued multidisciplinary research by adopting a single research objective: sea-level rise related water security threats, resulting in a more holistic view of problems and potential solutions. In fragmenting research, policy-makers can fail to understand how multiple issues can materialize from one driver. By combining efforts, an integrated assessment of water security threats in the lower Nile is formulated, offering policy-makers a clearer picture of inter-related issues to society and environment. The main issues identified by each project (land subsidence, saline intrusion — CLIMB; water supply overexploitation, land loss — WASSERMed; employment and housing security — CLICO), are in fact related. Water overexploitation is exacerbating land subsidence and saline intrusion, impacting on employment and placing additional pressure on remaining agricultural land and the underdeveloped housing market. All these have wider implications for regional development. This richer understanding could be critical in making better policy decisions when attempting to mitigate climate and social change impacts. The CLIWASEC clustering offers an encouraging path for the new European Commission Horizon 2020 programme to follow. •The EU FP7 CLIWASEC cluster of projects are introduced.•Interdisciplinary assessment of sea level rise impacts to Nile delta is presented.•Sea level rise causes complex, inter-related issues in the region.•CLIWASEC clustering enriched the conclusions compared with singular analysis.•Policy makers have more of the ‘bigger picture’, and are better informed.